Impact of type 2 diabetes mellitus and physical activity on medication costs in older adults. (22nd August 2019) - Kikuti‐Koyama, Kelly Akemi; Monteiro, Henrique Luiz; Ribeiro Lemes, Ítalo; de Morais, Luana Carolina; Fernandes, Rômulo; Turi‐Lynch, Bruna; Codogno, Jamile
Summary: Introduction: The high prevalence of diabetes mellitus leads to high costs of medication for treatment and the practice of physical activity, as well as reducing the risks of diabetes mellitus is able to substantially mitigate costs. To investigate the impact of diabetes mellitus on costs of medication and identify whether physical activity can influence the relationship between diabetes mellitus and costs of medication. Methods: The sample consisted of adults enrolled in five basic healthcare units. The presence of diabetes mellitus and habitual physical activity were assessed by a questionnaire, the quantity of medication used was evaluated according to the medical records, and medication costs, through receipts. Findings: Individuals with diabetes mellitus from baseline presented higher body weight ( P value = .001) and lower levels of physical activity ( P value = .014). The presence of diabetes mellitus was positively related to costs of medication for diseases of the circulatory system ( β = 4.89), endocrine, nutritional, and metabolic diseases ( β = 109.72), and total costs of medication ( β = 113.41). The impact of diabetes mellitus was attenuated by physical activity. Conclusion: It was identified that diabetes mellitus has a significant impact on public costs with medication, and physical activity was effective in reducing health costs independently of diabetes mellitus by less than 1%.